Characterization of Maithili duck in middle Gangetic plain of Bihar - KAMAL, REENA; C, CHANDRAN P; AMITAVA, DEY; P, BHATT B (The Indian Journal of Animal Sciences, 2020)
A study was conducted in middle Gangetic plain of Bihar to evaluate the smallholder duck production systems in the regions. A total of 70 duck farmers in Bihar were selected for this study. The information were collected by using standard questionnaire and an interview. The majority of the farmers (60%) belonged to middle-aged category. Majority of duck rearers in Bihar rears the duck more than 20 years. The average flock size was 6.1±0.33. Ducks were raised under semi-intensive management system and mostly depend on scavenging for their nutritional needs in the study area. About 88.6% farmers provided some kind of housing for their ducks, usually constructed mainly from simple and locally available materials in their backyard. Farmers did not possess any permanent shelter. Majority of the farmers (94.29%) did not vaccinate against the diseases of ducks due to unavailability. In both drake and duck, body carriage was slightly upright and Bill shape was horizontal. The ducks are raised both for meat and eggs. The average annual egg production per duck was ranged to be 30–60 eggs per annum. The average body weight of drake and duck were 1.40±0.07 and 1.37±0.08 kg, respectively. The predominant plumage colours of the Head, neck, breast, wing, and tail were brown (43.75%), brown and white mix with or without white ring (53.75%), brown (80.00%), brown, black and white mix (57.50%) and brown (40.00%) respectively. The dominant bill colour were yellow (43.75%) and web colour were orange (56.25%) respectively in Maithili duck. Mosaic plumage colour pattern was predominant in Maithili duck of Middle gangetic plain.